Adverse effects of long-term drain placement and the importance of direct aspiration: a retrospective cohort study. (January 2023) - Okui, J.; Obara, H.; Uno, S.; Sato, Y.; Shimane, G.; Takeuchi, M.; Kawakubo, H.; Kitago, M.; Okabayashi, K.; Kitagawa, Y.
Summary: Background: Long-term placement of prophylactic drains may result in retrograde infections. Aim: To investigate the association between the timing of drain removal and clinical outcomes. Methods: This retrospective, single-centre cohort study evaluated 110 patients who underwent elective gastrointestinal or hepatopancreatobiliary surgery and developed subsequent organ/space surgical site infection (SSI) between 2016 and 2020. The difference between the culture-positive species of prophylactic drains and direct aspiration was evaluated; whether the prophylactic drains functioned effectively at the time of SSI diagnosis; and whether the empirical antibiotics administered before drainage were effective against all the detected bacteria. Finally, clinical outcomes were compared between early (i.e. cases wherein the prophylactic drain had already been removed or replaced at the time of SSI diagnosis) and late (removal after diagnosis) drain removal. Findings: The prophylactic drains functioned effectively in only 27 (25%) patients at the time of SSI diagnosis. Due to the results of direct aspiration cultures, 43% of patients required antibiotic escalation. The median time to drain removal or first replacement was seven postoperative days. The early removal group included 43 patients (39%). Compared with early removal, late removal resulted in a higher frequency of vancomycin use (7.0% vs 22.4%; P  = 0.037). Conclusion: Prolonged prophylactic drain placement is associated with complicated infections requiring vancomycin; therefore, the drains should be removed as soon as possible. Additionally, obtaining the cultures of direct aspiration should be actively considered, as escalation of antimicrobial therapy is often performed based on culture results.